The Role of Pregnancy-Associated Hormones in the Development and Function of Regulatory B Cells - Muzzio, Damián; Zygmunt, Marek; Jensen, Federico (Frontiers in Endocrinology, 2014)
During mammalian pregnancy, highly specialized mechanisms of immune tolerance are triggered in order to allow the semi-allogeneic fetus to grow within the maternal uterus in harmony with the maternal immune system. Among other mechanisms, changes in the endocrine status have been proposed to be at least part of the machinery responsible for the induction of immune tolerance during pregnancy. Indeed, pregnancy-associated hormones, estradiol, progesterone and human chorionic gonadotropin are known to confer immune suppressive capacity to innate as well as adaptive immune cells. Regulatory B cells, a sub-population of B-lymphocytes with strong immunosuppressive functions, were shown to expand during pregnancy. Furthermore, it is well known that some women suffering from multiple sclerosis, significantly improve their symptoms during pregnancy and this was attributed to the effect of female sex hormones. Accordingly, estradiol protects mice from developing experimental autoimmune encephalomyelitis by triggering the expansion and activation of regulatory B cells. In this review we discuss different mechanisms associated with the development, activation and function of regulatory B cells with a special focus on those involving pregnancy-associated hormones.